Delta MELD as a predictor of early outcome in adult-to-adult living donor liver transplantation - Acar, Şencan; Akyıldız, Murat; Gürakar, Ahmet; Tokat, Yaman; Dayangaç, Murat (Turkish Journal of Gastroenterology, 2020)
Background/Aims: An increased post-operative mortality risk has been reported among patients who undergo living donor liver transplantation (LDLT) with higher model for end-stage liver disease (MELD) scores. In this study, we investigated the effect of MELD score reduction on post-operative outcomes in patients with a high MELD (≥20) score by pre-transplant management. Materials and Methods: We retrospectively analyzed 386 LDLT cases, and patients were divided into low-MELD (<20, n=293) vs. high-MELD (≥20, n=93) groups according to their MELD score at the time of index hospitalization. Patients in the high-MELD group were managed specifically according to a treatment algorithm in an effort to decrease the MELD score. Patients in the high-MELD group were further divided into 2 subgroups: (1) responders (n=34) to pre-transplant treatment with subsequent reduction of the MELD score by a minimum of 1 point vs. (2) non-responders (n=59), whose MELD score remained unchanged or further increased on the day of LDLT. Responders vs. non-responders were compared according to etiology, demographics, and survival.